Advances in Web-Based Learning - ICWL 2012 11th International Conference, Sinaia, Romania, September 2-4, 2012. Proceedings - Popescu, Elvira; Li, Qing.; Klamma, Ralf.; Leung, Howard; Specht, Marcus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 11th International Conference on Web-Based Learning, ICWL 2012, held in Sinaia, Romania, in September, 2012. The 28 revised full papers presented together with 10 short papers were carefully reviewed and selected from about 105 submissions. The papers are organized in topical sections on Computer Supported Collaborative Learning, Web 2.0 and Social Learning Environments; Personal Learning Environments; Learning Objects$1 (BManagement and Ontologies; Game-Based Learning; Personalized and Adaptive Learning; Feedback, Assessment and Learning Analytics; Design, Model and Implementation of E-Learning Platforms and Tools; Pedagogical Issues, Practice and Experience Sharing.s
Computer Supported Collaborative Learning, Web 2.0 and Social Learning Environments -- Personal Learning Environments -- Learning Objects$1 (BManagement and Ontologies -- Game-Based Learning; Personalized and Adaptive Learning; Feedback, Assessment and Learning Analytics -- Design, Model and Implementation of E-Learning Platforms and Tools -- Pedagogical Issues, Practice and Experience Sharing.s
Keywords: Computer science; Information storage and retrieval systems; Multimedia systems; Artificial intelligence; Education; Computer Science; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Computers and Education